Arquímedes y la palanca en 90 minutos - Strathern, Paul, 1940-; Corriente Basús, Antón; Strathern, Paul, 1940- (Tres Cantos, Madrid, España : Siglo XXI de España Editores, S.A., 2014)
Presents an overview of a man who was a scientific and mathematical genius and explains his knowledge and inventions together with their historical and scientific context.
Online resource; title from ePub title page (Digitalia, viewed June 28, 2017)
Keywords: Archimedes; Mathematicians -- Biography; Mathematics, Ancient; Mathematics, Greek; Electronic books